Numerical investigation of the impact of coating layers on RDF combustion and clinker properties in rotary cement kilns. (1st January 2021) - Pieper, C.; Wirtz, S.; Schaefer, S.; Scherer, V.
Graphical abstract: Highlights: CFD-simulations of rotary cement kilns considering coating layers are conducted. Numerical models for RDF, coating and clinker bed are presented and combined. The impact of coating regions on RDF combustion and clinker properties is investigated. Light and evenly distributed coating profiles are found to be beneficial for the process. Heavy and locally concentrated coating can result in a high free lime content of 2 wt%. Abstract: The formation of regions of solid coating, where agglomerated clinker material adheres to the refractory lining of the kiln wall, is very common during cement clinker production. While a thin coating layer protects the refractory lining, strong deposit formation can impair the material flow through the kiln. In this study, the impact of these coating layers on the clinker production process within a rotary kiln is investigated with CFD simulations. The fuel injected at the main burner is a mixture of pulverized coal and refuse derived fuel (RDF). Advanced models were developed to accurately describe the trajectories and thermal conversion of non-spherical RDF particles in the gas phase. These models are based on a detailed fuel analysis of major RDF fractions. A blocked-off region approach is used to consider different coating profiles within the simulation domain. The thermochemical processes in the clinker bed of the kiln are approximated with a one-dimensional model that calculates heat and mass exchange with the gas phase, the incorporation of fuel ashes into the bed and the chemical-mineralogical reactions of the clinker. The blocked-off region approach is also employed to account for the clinker bed geometry in the kiln, which greatly depends on the considered coating profile. Two cases, one with a thin and evenly distributed coating profile and one with a thick and locally concentrated coating, are simulated. The resulting impact on RDF conversion, gas phase properties and clinker phase formation are assessed and compared to a reference case without any coating. Results show that the insulation effect of a thin coating profile increases the gas phase temperature in the kiln and helps to reduce the free lime content of the final clinker product. In the case of heavy coating, a temperature shift towards the solid material inlet of the kiln occurs, which outweighs the beneficial insulation effect of the coating in the sintering zone and leads to lower local gas phase temperatures. In combination with reduced clinker residence times, this results in a slight increase of the free lime content in the clinker.